Synthetic individual binaural audio delivery by pinna image processing. Issue 3 (26th August 2014) - Spagnol, Simone; Geronazzo, Michele; Rocchesso, Davide; Avanzini, Federico
Abstract : Purpose: – The purpose of this paper is to present a system for customized binaural audio delivery based on the extraction of relevant features from a 2-D representation of the listener's pinna. Design/methodology/approach: – The most significant pinna contours are extracted by means of multi-flash imaging, and they provide values for the parameters of a structural head-related transfer function (HRTF) model. The HRTF model spatializes a given sound file according to the listener's head orientation, tracked by sensor-equipped headphones, with respect to the virtual sound source. Findings: – A preliminary localization test shows that the model is able to statically render the elevation of a virtual sound source better than non-individual HRTFs. Research limitations/implications: – Results encourage a deeper analysis of the psychoacoustic impact that the individualized HRTF model has on perceived elevation of virtual sound sources. Practical implications: – The model has low complexity and is suitable for implementation on mobile devices. The resulting hardware/software package will hopefully allow an easy and low-tech fruition of custom spatial audio to any user. Originality/value: – The authors show that custom binaural audio can be successfully deployed without the need of cumbersome subjective measurements.